Association between implementation of a coordinated care pathway in idiopathic scoliosis patients and a reduction in perioperative outcome disparities. Issue 4 (10th December 2021) - Dela Merced, Philip; Vazquez Colon, Caroll; Mirzada, Ariana; Oke, Ayodele; Gal, Zsombor; Cheng, Jenhao; Oetgen, Matthew M.; Martin, Benjamin; Pestieau, Sophie R.; Cronin, Jessica A.
Abstract: Background: There are well‐documented racial and ethnic disparities in treatment and perioperative outcomes for patients with adolescent idiopathic scoliosis. Aims: We hypothesize that the implementation of a coordinated care pathway for pediatric patients undergoing posterior spinal fusion for adolescent idiopathic scoliosis may be associated with a reduction in racial and ethnic disparities in perioperative outcomes. Methods: This is a retrospective pre‐ and post‐test cohort study of patients who underwent posterior spinal fusion for adolescent idiopathic scoliosis at our institution between July 1, 2013 and August 5, 2019. We implemented a coordinated care pathway in March 2015. Patient demographics included age, race, ethnicity, weight, gender, insurance status, ASA class, time between the date surgery was ordered and the date surgery occurred, degree of scoliosis, and the number of spinal levels fused. The primary outcome was length of stay. The secondary outcomes included transfusion rates, pain scores, and postoperative complications. Multivariable regression models compared outcome medians across race/ethnicity. Disparities were defined as the difference in adjusted outcomes by race/ethnicity. Results: Four hundred twenty‐four patients underwent posterior spinal fusion for adolescent idiopathic scoliosis at our institution (116 prepathway and 308 postpathway). The median length of stay of Black patients was 1.0 day (95% CI: 0.4, 1.5; p  = .006) longer than White patients prepathway. Prepathway patients who self‐identified as Other had a 1.2 (95% CI: 0.5, 1.9; p  = .004) higher median average pain score on postoperative day 1 compared with White patients. On postoperative day 2, patients who identified as Other had 2.0 (95% CI: 0.8, 3.2; p  = .005) higher pain score compared with White patients prepathway. Postpathway, there were no significant differences in outcomes by race/ethnicity. Conclusions: Our study supports the hypothesis that use of a coordinated care pathway is associated with a reduction in racial and ethnic disparities in length of stay and pain scores in pediatric patients undergoing posterior spinal fusion.